Molecular variability in Pythium aphanidermatum causing rhizome rot of ginger - and YASHODA R. HEGDE, SHALINI D. SAGAR, SRIKANT KULKARNI (Indian Phytopathology, 2009)
In isozymatic analysis, i.e., peroxidase, polyphenoloxidase and catalase, polymorphic banding pattern was observed in some isolates of Pythium aphanidermatum indicating variation in the pathogen. Molecular variability among 12 isolates of the pathogen was studied by using PCR based RAPD method. RAPD analysis of using 40 random primers, resulted in 313 amplicon levels, out of which 245 polymorphic bands levels were observed. The cumulative analysis of similarity values placed 12 isolates in 2 clusters. The results showed the possibility of using RAPD technique to distinguish variability among the isolates of P. aphanidermatum. This information could then be used to determine specific primers that would allow the identification of the fungus directly from plant material or in the soil.